Mengenal Perilaku Bullying di Sekolah - Wiwied Widianti (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2019)
This article illustrates how bullying behavior occurs in the world of education, especially schools. The method used in this study is descriptive analysis, by looking for things related to bullying that occur at school. Bullying is one of the problems in school and is difficult to eliminate. Bullying has become a widespread concern, but bullying has not shown a decline. There are many negative effects caused by bullying, both from people who suffer from bullying and victims of bullying. Guidance and counseling teachers as important actors in the world of education need to obtain information to overcome this problem. Because if the behavior of bullying has become a common thing to do, it will result in the education process not being good. Everyone is free to take action that will cause disruption of the education process at school. In conditions like this, guidance and counseling are very important in improving and eliminating the bullying behavior that exists in school. That way, the conditions that should be created in the school environment, namely mutual respect and respect.